Revision of the Miocene shrimp Callianassa kerepesiensis Müller, 1976 (Malacostraca, Decapoda), with a description of a new species - Hyžný, Matúš (Zootaxa, 2020)
Based on the re-examination of the type and additional material of a fossorial shrimp Callianassa kerepesiensis Müller, 1976, from the middle Miocene (Badenian) of Hungary, the species is re-assigned to Calliax de Saint Laurent, 1973. Additionally, Callianassa reinhardpalorum sp. nov. is described based on the morphologically similar cheliped elements, classified at one time as C. cf. kerepesiensis. Both species, Callianassa reinhardpalorum sp. nov. and Calliax kerepesiensis comb. nov., have extant congeners inhabiting modern Mediterranean Sea and north-east Atlantic. The sedimentology of the localities with remains of the studied fossil taxa corresponds with the environmental preferences of their extant congeners, suggesting they inhabited marine settings with slightly changing salinity and the water depth not exceeding 20 m.